Enabling smart urban redevelopment in India through floor area ratio incentives. - Apoorva,Shenvi (Manila Asian Development Bank, 2018)
Urbanization in India is expected to peak in 2050. The Smart Cities Mission was launched in 2015 to transform and improve livability in urban areas in the country.
Keywords: Industrialization -- South Asia,India; Urban development; Electronic books